THE ETERNAL RETURN IN LOBO ANTUNES’ TRILOGY: THE SUBJECT AND ITS ADRIFT MASKS - Mello, Carla Cristiane (Revista Desassossego, 2014)
This article brings into focus the trilogy of Portuguese writer António Lobo Antunes: "Memória de Elefante" (2007), "Os cus de Judas" (2006) and "Conhecimento do Inferno" (2007), seeking to identify a perspective of the Nietzschean concept of the eternal return in these narratives. Such characteristic can be noticed through the memory of the trauma, melancholy and resentment of the character who browses these books in a cyclic pursue for his own salvation. This salvation, perhaps, can only take place through language, of the echo that brings reminiscences of the narrator-character’s everyday life. Or, narratives of resentment and sadness due to the loss of identity and fragmentation of the character, who lived in an era notably marked in the postcolonial Portuguese narratives, and which has dwelt in the shadow of Salazar and his 40-year fascist dictatorship. Therefore, the character shows and hides at the same time, in order to bring out a different look about himself and the world around him, framing through poetic words the raw weight of a life enclosed in language so to escape madness, or to lose himself in it.